FURTHER STUDY ON TWO SPECIES OF LOACH FISHES (Cypriniformes: Nemacheilidae: Nemacheilus) BASED ON MORPHOLOGY AND MOLECULAR DATA - Dwi Anggorowati Rahayu; Sunu Kuntjoro; Widowati Budijastuti; Winarsih Winarsih; Reni Ambarwati; Endik Deni Nugroho; Abdul Basith; Nia Kurniawan; Haryono Haryono (SEAMEO BIOTROP, 2023)
The identities of two local loaches, Nemacheilus chrysolaimos (Valenciennes, 1846) and N. fasciatus (Valenciennes, 1846) from six rivers, were obtained through a comprehensive examination of their morphology and molecular characteristics in Biltar Regency, East Java, Indonesia. Therefore, this study identified Nemacheilus spp. from Blitar based on morphology and partial sequence of COI. The meristic data obtained for N. chrysolaimos included DII. 7–8 (dorsal fin), AI. 3–5 (anal fin), PI. 9 (pectoral fin), VI. 6–7 (ventral fin), and C. 17 (caudal fin). On the other hand, N. fasciatus exhibited the following meristic data, namely D II 7–8 (dorsal fin), AI. 6 (anal fin), PI. 9–10 (pectoral fin), VI. 6–7 (ventral fin), and C. 17 (caudal fin). A significant difference was observed in the morphometric characteristics of N. fasciatus across various sampling sites, as determined by the Kruskal-Wallis Test. Furthermore, the nucleotide base composition sequences of Nemacheilus spp. consisted of Thiamine (T), Cytosine (C), Adenine (A), and Guanine (G) with a mean of 29.565%, 32.023%, 23.88%, and 16.244%. Maximum Likelihood (ML) and Minimum Evolution (ME) phylogenetic analysis was also conducted using the Kimura 2 Parameter model to establish two major clades on Nemacheilus spp. and one out-group significantly different from the Nemacheilus spp. The results showed that these major clades exhibited a close relationship at 100% bootstrap support and were grouped under the genus Nemacheilus. The study on Nemacheilus spp. from the Blitar locality differentiated COI sequences between N. fasciatus and N. chrysolaimos. Additionally, N. chrysolaimos, as inferred from reference sequences, was identified as the ancestral species to N. chrysolaimos MZB 26540 and MZB 26539. ABGD analyses, employing a prior maximal distance of 0.025, also indicated the separation of these species into distinct partitions. The integration of morphology and genetic data for Nemacheilus spp. should provide valuable insights for future genetic population studies and conservation initiatives.